Long-wavelength photolysis of amino acid 6-(methoxy-2-oxo-2H-naphtho[1,2-b]pyran-4-yl)methyl esters - Piloto, Ana M. (2011)
Ester derivatives of fused 4-methyl-6-methoxy-2-oxo-2H- naphtho[1,2-b]pyran, using valine and phenylalanine as model bifunctional molecules were synthesised, to assess its applicability as a photocleavable protecting group, for solution phase organic synthesis and in caging applications, at longer wavelengths. The behaviour of the corresponding derivatives towards photolysis was evaluated by irradiation in mixture of HEPES buffer and acetonitrile or methanol, in a photochemical reactor at 350 and 419 nm, followed by HPLC/UV monitoring. Time-resolved fluorescence measurements were used to elucidate the dynamics.